2017
DOI: 10.1038/bmt.2016.361
|View full text |Cite|
|
Sign up to set email alerts
|

Latin America: the next region for haematopoietic transplant progress

Abstract: Haematopoietic cell transplant activity in the 28 countries comprising Latin America is poorly defined. We conducted a voluntary survey of members of the Latin American Bone Marrow Transplantation Group regarding transplant activity 2009-2012. Collated responses were compared with data of transplant rates from the Worldwide Network for Blood and Marrow Transplantation for other geographic regions. Several socio-economic variables were analysed to determine correlations with transplant rates. In total, 94 teams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…Despite important progress in HSCT in this region, access to HSCT for PID varies dramatically across Latin American countries and even within the same country. A survey performed in 2015 showed that only nine countries had transplanted patients with PID (Brazil, Argentina, Mexico, Uruguay, Peru, Colombia, Chile, Venezuela, and Costa Rica) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite important progress in HSCT in this region, access to HSCT for PID varies dramatically across Latin American countries and even within the same country. A survey performed in 2015 showed that only nine countries had transplanted patients with PID (Brazil, Argentina, Mexico, Uruguay, Peru, Colombia, Chile, Venezuela, and Costa Rica) [18].…”
Section: Introductionmentioning
confidence: 99%
“…HSCT is an economically viable treatment of hematologic diseases in well-resourced countries, and recently it has become feasible to perform this procedure in developing countries. 7 , 9 - 11 …”
Section: Discussionmentioning
confidence: 99%
“…Currently, updated HSCT statistics in Mexico have not been published; a recent study performed in Latin America 11 reported a transplantation rate of 127 and 97 allogeneic and autologous transplantations in 2012, respectively. Our institution and the National Cancer Institute, along with other governmental centers, are the primary tertiary/referral hospitals to perform HSCT, and at the moment, approximately 20% of HSCT in Mexico is performed at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…The group of HSCT evaluated in this study is characterized by a predominant use of BM as cell source, which reflects the clinical practice in Latin American countries, such as Brazil. 53 , 54 Economic constraints, as well as a high number of transplants for marrow failure syndromes, where the use of BM is chosen over other cell sources, are responsible for the disparity with developed countries, where PB predominates as cell source. In fact, in our work, BM failure syndromes (severe aplastic anemias and myelodysplastic syndromes) account for 22.5% of diagnoses.…”
Section: Discussionmentioning
confidence: 99%